10.1016/0967-0653(93)93954-p (CrossRef Listing of Deleted DOIs, 2000)
Background Psychiatric hospitalizations are a major driver of mental health-related health care costs, with readmission risk and service utilization being highest in the months following discharge. Scalable, low-cost postdischarge interventions that reduce inpatient utilization are therefore of high policy relevance. Objective This secondary exploratory economic study used linked administrative health care utilization data to evaluate the economic impact of supportive text messaging (SMS), alone and in combination with peer support services (PSS), following discharge from acute psychiatric care. Methods This secondary exploratory economic evaluation was conducted alongside a pragmatic stepped-wedge cluster randomized trial in Alberta, Canada. Adults discharged from acute psychiatric inpatient care received treatment as usual (TAU), SMS, or SMS with or without PSS. Direct health system costs, including hospital care and physician costs, were assessed using administrative data for 6 months and 12 months before and after the index admission. Difference-in-difference analyses were used to estimate cost changes between groups. Results At 6 months post discharge, the period of greatest new costs, participants receiving SMS experienced a significant reduction in hospital care costs compared with TAU (mean difference-in-differences -$7147; 95% CI -$12,388 to -$1906; P=.01). Total health care costs were also significantly lower in the SMS group at 6 months (-$8160) relative to TAU. Sensitivity analyses demonstrated that the direction and statistical significance of the primary findings remained stable across alternative intervention costing assumptions and analytic specifications. No significant cost differences were observed at 12 months. The addition of peer support did not result in incremental cost savings at either time point. Conclusions SMS was associated with significant reductions in hospital care and total health care utilization costs during the 6-month postdischarge period compared with TAU. These findings support the integration of cost-effective and scalable digital interventions into routine psychiatric discharge pathways to help improve system efficiency in publicly funded health systems.